A GLOBAL MODEL FOR THE EARLY DIAGENESIS OF ORGANIC CARBON AND ORGANIC PHOSPHORUS IN MARINE SEDIMENTS - Tromp T.K.; Van Cappellen P.; Key R.M. (My University, 1995)
Sediments are the main repository in the oceanic cycles of carbon (C) and phosphorus (P). In order to relate the deposition of organic C and organic P from the water column, and ultimate burial in sediments, we present a model for the early diagenesis of organic matter in marine sediments. This general diagenetic model was developed for inclusion in global circulation models and is based on a single master variable, the sedimentation rate. The processes included are sediment advection, particle mixing by bioturbation, porewater diffusion, organic matter degradation by aerobic respiration, sulfate reduction, and methanogenesis. Deposition fluxes of organic C and organic P, and the bottomwater concentrations of O2 and SO=4 are used as input for the sediment model. First-order kinetics are assumed for the degradation of organic C and organic P (one-G model).Despite the model's simplicity, the model quantitatively reproduces the rates of organic matter oxidation and the burial fluxes of organic C and P. The predicted trends of oxygen penetration depth and the relative importance of oxygen and sulfate reduction are in good agreement with field observations. The model appears to account for the critical biogeochemical and transport processes that control the fate of organic matter in sediments.